Experience with the ketogenic diet in premature neonates. Issue 1 (1st December 2022) - Phitsanuwong, Chalongchai; Kim, Jeong‐A; Schimpf, Stephanie; Nordli, Douglas R.
Abstract: The ketogenic diet is a time‐tested, potent, nonpharmacological treatment of epilepsy. However, the use of the ketogenic diet in premature neonates with epilepsy has not been previously reported. We share our experience with the use of ketogenic diet therapy in two premature neonates. Two identical twin premature neonates with SCN2A ‐related developmental and epileptic encephalopathy, whose seizures were refractory to multiple anti‐seizure medications, were started on the classic ketogenic diet at the conceptual age of 35 weeks. Ketosis was achieved and maintained (range 2‐5 mmol/L of serum beta‐hydroxybutyrate level). Seizure frequency was significantly reduced (>90% reduction in both patients), and some anti‐seizure medications were able to be discontinued. Initial transient weight loss and one episode of asymptomatic hypoglycemia were observed and corrected. The ketogenic diet was found to be a safe, well‐tolerated, and effective treatment for seizures in two premature neonates. The side effects are tolerable and correctable. The ketogenic diet, therefore, is a treatment option for refractory seizures in this age group, when administered under expert guidance.